Kinetics of Hydrogenation of Lauric Acid in a Batch Slurry Reactor Using Ru-Sn/TiO2 Catalyst - Shinde, S.B.; Deshpande, R.M. (Asian Journal of Chemistry, 2012)
Ru-Sn catalyst was prepared in-house by impregnation method. This catalyst was found to be stable for four recycles. The rate of hydrogenation of lauric acid (LAC) using Ru-Sn/TiO2 catalyst was found to be linearly dependent on catalyst loading, lauric acid concentration and hydrogen partial pressure. The rate data obtained from kinetic study were fitted to simple rate equation based on Langmuir-Hinshelwood (L-H) type model. Based on kinetic data the hydrogenation of lauric acid over Ru-Sn/TiO2 catalyst is proposed to occur by dual site mechanism the activation energy for hydrogenation of lauric acid to lauryl alcohol (LAOH) using Ru-Sn/TiO2 catalyst was found to be 77.2 kJ/mol.